Pasteur, Vaccines, and the Refusal to Become Fully Vaccinated in the Midst of the COVID-19 Pandemic - Pavia, Charles S. (Frontiers in Public Health, 2022)
Vaccines are one of the most effective public health measures that are designed to prevent serious illness caused by a wide variety of infectious agents, which have become especially important in light of the coronavirus disease 2019 (COVID-19) pandemic. Despite the favorable outcomes associated with vaccine development and use, a new wave of hesitancy to get vaccinated has emerged that threatens the control or quick elimination of the highly contagious and life-threatening infection caused by SARS-CoV-2. At the forefront of the current anti-vaccine movement is the dissemination of false and misleading information. This essay explores the primary reasons, which also includes an historical connection, behind this anti-vaccine sentiment, and proposes several possible and realistic interventions that could be implemented to counter this notion and significantly improve vaccine acceptance, especially among young people.